The hunger games. Mockingjay. Part 1 [videorecording(DVD)] - Lawrence, Jennifer, 1990-; Hutcherson, Josh; Hemsworth, Liam, 1990-; Sutherland, Donald, 1935-; Collins, Suzanne (Lions Gate Films, 2015)
With the games destroyed and Peeta captured, Katniss becomes the symbol of rebellion while trying to rescue Peeta from the capitol.